2022
DOI: 10.55713/jmmm.v32i4.1527
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of lutein dye from Tagetes erecta garland waste for green dyeing of hemp fabric using response surface methodology

Abstract: Large quantities of discarded flowers from religious observances are left at temples and other places of worship, causing global disposal and environmental issues. Recycling and transforming such organic waste into value-added products is one of the most effective and beneficial solutions to the problem. The main goal of this study is to convert the most abundant temple wastes of marigold (Tagetes erecta) flowers into an eco-friendly dyestuff for the textile industry. Our study assessed the suitability of dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to Nur Fadzli et al [11], Tagetes erecta L. (Mexican variety) was used as the source of natural dyes. According to Lohar and Jayoti [12], marigold is one of the main sources of carotenoids that can produce high color output, namely lutein pigment, which contains the vertical antennae of carotenoids and can create unique colors, such as yellow to orange [13]. According to previous studies, it was found that the extract from tagetes erecta is non-toxic and harmful to the environment [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Nur Fadzli et al [11], Tagetes erecta L. (Mexican variety) was used as the source of natural dyes. According to Lohar and Jayoti [12], marigold is one of the main sources of carotenoids that can produce high color output, namely lutein pigment, which contains the vertical antennae of carotenoids and can create unique colors, such as yellow to orange [13]. According to previous studies, it was found that the extract from tagetes erecta is non-toxic and harmful to the environment [12,13].…”
Section: Introductionmentioning
confidence: 99%